2014
DOI: 10.1523/jneurosci.3625-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

In VivoIdentification of Eugenol-Responsive and Muscone-Responsive Mouse Odorant Receptors

Abstract: Our understanding of mammalian olfactory coding has been impeded by the paucity of information about the odorant receptors (ORs) that respond to a given odorant ligand in awake, freely behaving animals. Identifying the ORs that respond in vivo to a given odorant ligand from among the ϳ1100 ORs in mice is intrinsically challenging but critical for our understanding of olfactory coding at the periphery. Here, we report an in vivo assay that is based on a novel gene-targeted mouse strain, S100a5-tauGFP, in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 52 publications
3
57
1
Order By: Relevance
“…S3.3). This response is consistent with a recent report (27), in which OR5AN1 was identified as a human muscone OR, based on homology to the mouse OR MOR215-1, functionally cloned from muscone-responsive glomeruli; a second report on OR5AN1 as the only functional human homolog of mouse muscone ORs in vivo (54); and a third report that only a small number of receptors are thought to be involved in sensing musk odor (55). Our screening and the following confirmation experiments did not reveal any human OR that responded to only one, two, or three of the four isotopomers of 1.…”
Section: Response Of a Human Musk Or To Deuterated And Nondeuteratedsupporting
confidence: 92%
See 1 more Smart Citation
“…S3.3). This response is consistent with a recent report (27), in which OR5AN1 was identified as a human muscone OR, based on homology to the mouse OR MOR215-1, functionally cloned from muscone-responsive glomeruli; a second report on OR5AN1 as the only functional human homolog of mouse muscone ORs in vivo (54); and a third report that only a small number of receptors are thought to be involved in sensing musk odor (55). Our screening and the following confirmation experiments did not reveal any human OR that responded to only one, two, or three of the four isotopomers of 1.…”
Section: Response Of a Human Musk Or To Deuterated And Nondeuteratedsupporting
confidence: 92%
“…; therefore, muscone may be recognized by only a small set of ORs, including OR5AN1 in humans, and genetic variation in these receptors may cause muscone anosmia" (27). McClintock et al (54) identified five highly related ORs, including MOR215-1, that are likely to be activated by muscone in freely behaving mice, supporting multiple muscone receptors. Importantly, however, the only functional human counterpart of these ORs is OR5AN1.…”
Section: Discussionmentioning
confidence: 99%
“…To address whether the reduction in ciliary OR accumulation affected the function of OSNs, we analyzed the S100 calcium binding protein A5 (S100A5) that is transiently expressed to high levels in odorant-stimulated OSNs and that requires intact olfactory cilia to be expressed (22,23). In concordance with reduced olfactory transduction in vismodegib-treated mice we found that the number of S100A5-positive OSNs was reduced in vismodegib-treated mice compared with controls (Fig.…”
Section: Smo Inhibition Results In Decreased Expression Of the Odorant-mentioning
confidence: 84%
“…Both types of ORs are expressed by the olfactory sensory neurons (OSNs) of the main olfactory epithelium (MOE), which is the largest structure of the olfactory system. Although the odorant ligands recognized by most ORs remain unknown, in vitro and in vivo studies have recently been making rapid progress toward identification of pairings of odorants and ORs (McClintock et al 2014, Nara et al 2011). Odorant–OR pairing is combinatorial: each odorant activates multiple ORs, and higher concentrations of an odorant activate additional ORs (Malnic et al 1999, McClintock et al 2014, Nara et al 2011).…”
Section: Introduction: the Logic Of The Olfactory Systemmentioning
confidence: 99%
“…Although the odorant ligands recognized by most ORs remain unknown, in vitro and in vivo studies have recently been making rapid progress toward identification of pairings of odorants and ORs (McClintock et al 2014, Nara et al 2011). Odorant–OR pairing is combinatorial: each odorant activates multiple ORs, and higher concentrations of an odorant activate additional ORs (Malnic et al 1999, McClintock et al 2014, Nara et al 2011). Most ORs appear to be tuned toward specific odorants, or odorants with a specific physicochemical feature, but some ORs are broadly tuned and recognize many, structurally diverse odorants (Grosmaitre et al 2009, Nara et al 2011).…”
Section: Introduction: the Logic Of The Olfactory Systemmentioning
confidence: 99%